Data analysis of the mid-winter census of wintering aquatic birds on the territory of Ramsar sites along the Bulgarian Black Sea coast for the period 2012 – 2021 - Stoyanova, Aleksandra; Berberova, Ralitza (Annual of Natural Sciences Department, 2023)
Wetlands along the Bulgarian Black Sea coast are important wintering points for aquatic birds during the winter period, which is why the site is included in the mid-winter census, which is part of ornithological monitoring in our country. Based on the results obtained from it, an assessment of the ornithological status can be made and the environmental factors influencing it can be analyzed. The purpose of the study is to present a summary and analysis of census data on the species composition and number of waterfowl in the region of the Ramsar sites on the Bulgarian Black Sea coast for the period 2012 – 2021, which will confirm the ecological significance of these sites and the need for their protection.